Quasiperiodic Solutions of the Heisenberg Ferromagnet Hierarchy. Issue 3 (3rd July 2019) - Zhao, Peng; Fan, Engui, Temuerchaolu
Abstract : We present quasi-periodic solutions in terms of Riemann theta functions of the Heisenberg ferromagnet hierarchy by using algebro-geometric method. Our main tools include algebraic curve and Riemann surface, polynomial recursive formulation and a special meromorphic function.